IMPLIKASI JUDI ONLINE TERHADAP MORALITAS DAN EKONOMI UMAT: TINJAUAN HUKUM ISLAM - Siti Nurharirah; Irmayanti Kumara Tungga; Miliyanti; Syarifah Raehana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid advance me nt of digital te chnology has contribu te d to the wide spre ad Pre vale nce of online gambling across variou s le ve ls of socie ty. This Phe nome non not only cau se s significant financial losse s bu t also u nde rmine s The moral and spiritu al fou ndations of the Mu slim commu nity. This stu dy Aims to e xamine the implications of online gambling on morality and the E conomic we ll-be ing of the u mmah from the pe rspe ctive of Islamic law. The Re se arch adopts a qu alitative approach u sing library re se arch me thods, Focu sing on normative analysis of re le vant ve rse s of the Qu r’an, Hadiths, And classical as we ll as conte mporary Islamic le gal and e conomic lite ratu re . The findings indicate that online gambling falls u nde r the cate gory of almaisir, which is strictly prohibite d in Islam du e to its e le me nts of u nce rtainty (gharar), e xploitation, and harm to othe rs. Fu rthe rmore , online gambling Contribu te s to the de gradation of individu al morality, worse ns hou se hold Financial conditions, and can le ad to stru ctu ral pove rty. The re fore , e ffe ctive pre ve ntion and mitigation e fforts are e sse ntial and shou ld be imple me nte d throu gh le gal e nforce me nt, moral e du cation, and the stre ngthe ning of family and commu nity role s.